Policemen of the Tsar : Local Police in an Age of Upheaval - Abbott, Robert J. (Robert James), 1945- (Book collections on Project MUSE., 2022)
"Founded by Peter the Great in 1718, Russia's police were key instruments of tsarist power. In the reign of Alexander II (1855-1881), local police forces took on new importance. The liberation of 23 million serfs from landlord control, growing fear of crime, and the terrorist violence of the closing years challenged law enforcement with new tasks that made worse what was already a staggering burden. ("I am obliged to inform Your Imperial Highness that the police often fail to carry out their assignments and, when they do execute them, they do so poorly because of their moral corruption...") This book describes the regime's decades-long struggle to reform and strengthen the police. The author reviews the local police's role and performance in the mid-nineteenth century and the implications of the largely unsuccessful effort to transform them. From a longer-term perspective, the study considers how the police's systemic weaknesses undermined tsarist rule, impeded a range of liberalizing reforms, perpetuated reliance on the military to maintain law and order, and gave rise to vigilante justice. While its primary focus is on European Russia, the analysis also covers much of the imperial periphery, discussing the police systems in the Baltic Provinces, Congress Poland, the Caucasus, Central Asia, and Siberia"--